Super modules-based active QR codes for smart trackability and IoT: a responsive-banknotes case study - João F. C. B. Ramalho (Nature Portfolio, 2020)
Abstract The general use of smartphones assigns additional relevance to QR codes as a privileged tool to the Internet of Things (IoT). Crucial for QR codes is the evolution to IoT-connected smart tags with enhanced storage capacity and secure accesses. Using the concept of super-modules (s-modules) built from adjacent spatial multiplexed modules with regular geometrical shapes, assisted by colour multiplexing, we modelled and design a single QR code with, at least, the triple storage capacity of an analogous size black/white QR code, acting as a smart-tag ensuring restrict access and trackability. The s-modules are printed using luminescent low-cost and eco-friendly inks based on organic-inorganic hybrids modified by lanthanides with multiplexed colour emission in the orthogonal RGB space. The access to the restrict information is attained only under UV irradiation and encrypted for secure transmission. The concept of active QR codes for smart trackability and IoT was materialised through the development of a free friendly-user mobile app.